Status of Food and Nutrition in the Arabian Gulf Countries - Farouk El-Sabban (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2015)
The Arabian Gulf countries are also known as the Gulf Cooperation Council (GCC) countries. They consist of six countries that are located in the Arabian Peninsula or connected to it. The GCC was formed in 1981 and includes: Bahrain, Kuwait, Oman, Qatar, Saudi Arabia and United Arab Emirates (Figure 1). Combined, all these countries have a population of nearly 50 million - the largest of which is Saudi Arabia (30 million) and the smallest is of Bahrain (1.6 million). The discovery of oil in these countries in the last century has led them to enjoy the highest per capita income among countries of the world, with many socio-economic changes taking place. With the presence of wealth, many infrastructural and developmental projects were and are being planned. This increased the demand for manpower required, thus many migrant workers from many countries are found in these countries. While the total population in these countries is about 50 million, the ratio of citizens to noncitizens is variable. Available statistics show that percentages of noncitizens range from 32% in Saudi Arabia to 88% in the United Arab Emirates. The presence of different ethnic groups in GCC countries makes them enjoy a state of cultural diversity.